Inflammation in Depression - Novi Agung Rahmawati; Azimatul Karimah; Mustafa M Amin (Faculty of Medicine, Universitas Airlangga, 2021)
Depression is a chronic condition that imposes a substantial burden of disability globally. Three principal neurotransmitters (norepinephrine (NE), dopamine (DA), and serotonin (5-HT)) implicated the pathophysiology and treatment of depression. Clinical studies have found a signiﬁcant association between numerous pro-inﬂammatory cytokines with depressive symptoms, endocrine, and neurotransmitter systems. Here, we detail our current understanding about the role of inﬂammation in depression, the mechanisms that are involved, and show how it is possible to innovate and develop new therapeutics of depression in the ﬁeld of neuroinﬂammation.